UPAYA INDONESIA DALAM MENGHADAPI HAMBATAN TEKNIS PERDAGANGAN: SEAFOOD IMPORT MONITORING PROGRAM TERHADAP EKSPOR PERIKANAN INDONESIA KE AMERIKA SERIKAT TAHUN 2014-2018 - Fauziyah Sri Marlina; Yusnarida Eka Nizmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This essay examines the technical barriers to trade (TBT) issued by Indonesia’s  partner country, the United States of America, which raises the barrier on Indonesia fishery export. The discussion in this research is the effort of Indonesia on dealing with the TBT: Seafood Import Monitoring Program issued by United States of America. This research applies the Protecsionism theory by Friedrich List to analyze Indonesia's government efforts on protecting their domestic product. The perspective used by the researchers is the perspective of mercantilism which assumes that the international economy is merely not mutually benefical but contains conflict of interest. This circumstance allows the impact where one side lost is a blessing fo the other.As the result of this study, it is found that Indonesia's government withstands the trade barriers from the United States of America by conducting negotiations related to SIMP regulation. In order to minimize the disadvantage that might be occurred due to the SIMP enforcement, these negotiations did not the reach  the WTO negotiations stage but resolved bilaterally. Indonesia also demands capacity building assistance and time compensation which consequently allow them to study and fulfill traceabilty requirements in advance. Key Word: The United States of America, Indonesia, Technical Barriers, Traceability, Export